The CRESST Dark Matter Search - Seidel, W; Bravin, M; Bruckmayer, M; Bucci, C; Cooper, S; Distefano, P; Feilitzsch, F; Frank, T; Jochum, J; Keeling, R; Kraus, H; Loidl, M; et al. (2000)
We discuss the short- and long-term perspectives of the CRESST (Cryogenic Rare Event Search using Superconducting Thermometers) project and present the current status of the experiment and new results concerning detector development. In the search for elementary particle dark matter, CRESST is presently the most advanced deep underground, low-background, cryogenic facility. The basic technique involved is to search for WIMPs (Weakly Interacting Massive Particles) by the measurement of nonthermal phonons, as created by WIMP-induced nuclear recoils. Combined with our newly developed method for the simultaneous measurement of scintillation light, strong background discrimination is possible, resulting in a substantial increase in WIMP detection sensitivity. This will allow a test of the reported positive evidence for a WIMP signal by the DAMA Collaboration in the near future. In the long term, the present CRESST setup permits the installation of a detector mass up to 100 kg. In contrast to other projects, CRESST technology allows the employment of a large variety of detection materials. This offers a powerful tool in establishing a WIMP signal and in investigating WIMP properties in the event of a positive signal. © 2000 MAIK "Nauka/Interperiodica".